2019
DOI: 10.1088/1755-1315/343/1/012113
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain analysis of dry and wet cocoa beans

Abstract: Aims of this study is to analyze the comparison of the characteristics and performance of dry and wet cocoa bean supply chains. The analytical method used the characteristics and supply chain performance with qualitative descriptive analysis using the FSCN (Food Supply Chain Networking) analysis framework. The research results indicated that there are currently two cocoa bean supply chain models in East Luwu District, namely the Dry Cocoa Bean Supply Chain and the Wet Cocoa Bean Supply Chain. The dry cocoa bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The yield of cocoa beans per fruit did not show a significant difference between plants given organic fertilizers and plants given inorganic fertilizers but the use of organic fertilizers had a positive role in increasing cocoa productivity through its effect on bean formation [15]. The application of organic fertilizer had an effect on plant height, stem diameter, root length, plant fresh weight, and dry weight of cocoa plants [16].…”
Section: Wet and Dry Bean's Weightmentioning
confidence: 87%
“…The yield of cocoa beans per fruit did not show a significant difference between plants given organic fertilizers and plants given inorganic fertilizers but the use of organic fertilizers had a positive role in increasing cocoa productivity through its effect on bean formation [15]. The application of organic fertilizer had an effect on plant height, stem diameter, root length, plant fresh weight, and dry weight of cocoa plants [16].…”
Section: Wet and Dry Bean's Weightmentioning
confidence: 87%
“…According to Saing et al (2019) and Muhardi, Abdul Rauf and Effendy (2021), farmer organizations needed to be directed in the marketing and quality improvement of cocoa beans to create a well-performing chain marketing system that could provide added value for farmers. According to Ikhwan et al (2021), the good organizations can make better decisions on choosing facilities more efficiently, managing supplies efficiently and be can use the information itself to increase profits by implementing learning organizations.…”
Section: The Benefit Of Purchasing Unitmentioning
confidence: 99%
“…As a logistics reference model, SCM refers to the 5 (five) rules, namely the right type, right amount, right quality, right time and right price/cost (Nining Purwatmini, 2015). There were studies reported the application of SCM in cocoa beans industries such as the supply chain analysis of dry and wet cocoa beans (Saing et al, 2019), agriculture supply chain performance and added value of cocoa: a study in Kare Village, Indonesia (Indah et al, 2021), study on stakeholders position and role in supply chain of cocoa commodities (Muhammad Asir et al, 2019), the role of smallholder human resources on the performance of the supply chain of cocoa beans in Central Sulawesi Indonesia (Hattab et al, 2021) and so on.…”
Section: Introductionmentioning
confidence: 99%